2007
DOI: 10.1155/2007/47161
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Novel Amino-Acid Sequence Repeats inBacillus anthracisstr.AmesProteome Using Computational Tools

Abstract: We have identified four repeats and ten domains that are novel in proteins encoded by the Bacillus anthracis str. Ames proteome using automated in silico methods. A “repeat” corresponds to a region comprising less than 55-amino-acid residues that occur more than once in the protein sequence and sometimes present in tandem. A “domain” corresponds to a conserved region with greater than 55-amino-acid residues and may be present as single or multiple copies in the protein sequence. These correspond to (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The RADAR program is efficient for ab initio detection of repeats in the query sequence. Since repeats of larger lengths are domain repeats (Hemalatha, Rao, & Guruprasad, 2007), we considered the subset of proteins with repeat pairs of length >45 and having continuous PDB coordinates for the present analysis. These proteins were searched against pfam database (Punta et al, 2012) to assign their domains regions.…”
Section: Data-set and Identification Of Internal Repeatsmentioning
confidence: 99%
“…The RADAR program is efficient for ab initio detection of repeats in the query sequence. Since repeats of larger lengths are domain repeats (Hemalatha, Rao, & Guruprasad, 2007), we considered the subset of proteins with repeat pairs of length >45 and having continuous PDB coordinates for the present analysis. These proteins were searched against pfam database (Punta et al, 2012) to assign their domains regions.…”
Section: Data-set and Identification Of Internal Repeatsmentioning
confidence: 99%
“…The folded domains can either serve as modules for building up large assemblies or provide specific catalytic enzyme functions or bindings of the proteins. It has been found that repeats of a length >50 residues often correspond to conserved regions that are present in proteins as single or multiple copies for the function of the proteins (Hemalatha et al, 2007). Our analysis of sequence repeats of the proteins with known 3D structures in the PDB (Berman et al, 2014) has shown that they retain similar folds in spite of divergences, in order to conserve the structure and function of the proteins and, repeats that are in the single/two domains from the same family contain conserved motifs for the function of the proteins (Mary Rajathei and Selvaraj, 2013).…”
Section: Introductionmentioning
confidence: 99%